Inotrope Use among Extremely Preterm Infants in Canadian Neonatal Intensive Care Units: Variation and Outcomes - Wong, Jonathan; Shah, Prakesh S.; Yoon, Eugene W.; Yee, Wendy; Lee, Shoo; Dow, Kimberly (American Journal of Perinatology, 2015)
Objective To compare neonatal outcomes between infants who received inotropes and those who did not, and identify variation in inotrope use.Study Design Retrospective review of data from neonates < 29 weeks gestation collected by the Canadian Neonatal Network during 2003 to 2010. After controlling for confounders and maternal/infant characteristics, rates of mortality and major morbidity were compared between those who received inotropes on days 1 and 3 of admission and those who did not. Rate of inotrope use was compared between sites.Results Inotropes were administered to 772 (10%) of the 7,913 neonates. Infants who received inotropes had significantly higher illness severity, surfactant use, and need for mechanical ventilation. Inotrope use was also associated with significantly higher rates of mortality (adjusted odds ratio [AOR] = 2.05 [1.64, 2.57]), retinopathy of prematurity (AOR = 2.04 [1.54, 2.71]), intraventricular hemorrhage (AOR = 1.59 [1.29, 1.93]), bronchopulmonary dysplasia (AOR = 1.38 [1.11, 1.72]), and necrotizing enterocolitis (AOR = 2.06 [1.59, 2.67]). Rates of inotrope use varied significantly between participating sites (0–36%; AOR = 0 [0, 0.1]–7.7 [2.9, 21]).Conclusion Risk of mortality and major morbidities were significantly higher in neonates who received inotropes. Inotrope use varied significantly among Canadian neonatal intensive care units.
Keywords: infant; premature; inotrope; mortality; morbidity; variation